Ultrasound-targeted microbubble destruction: a prospective strategy for treating cardiovascular disease - Yang, Shuting; Zhang, Rong; Zhang, Huali; Lu, Yongping (Frontiers in Cardiovascular Medicine, 2025)
In China, the healthcare burden of cardiovascular diseases (CVDs) will continue to rise due to the pressure of the aging population, which has posed higher demands for CVDs prevention and treatment. Ultrasound-targeted microbubble destruction (UTMD) is an ultrasound-triggered drug delivery technique based on microbubbles. This technique utilizes the principles of cavitation and sonoporation to enhance the delivery of genes or drugs to target tissue. This review article will provide an overview of studies using UTMD to treat CVDs over the last decade. In light of these studies, we underscore the potential therapeutic targets and delineate the practical substances that can be loaded onto microbubbles. Additionally, a discussion is provided regarding the limitations and prospects of this field.